Five Years Data of Vaginal Swab Examination on Sexual Assault Cases inWest Java Top Referral Hospital, Indonesia - Febriastry, Machrani; Sayusman, Chevi; Zulvayanti, Zulvayanti (Althea Medical Journal, 2017)
Background: Vaginal swab test is one of the way to prove that penile penetration has occurred by detection of spermatozoa or seminal fluid components inÂ  vaginal fluid of sexual assault victims. It is also used for detecting sexually transmitted infection (STI) inÂ  thevictims and identifying perpetratorsâ DNA. The objective of this study was to describe vaginal swab examination result on sexual assault cases in Dr. Hasan Sadikin General Hospital, Bandung so it can be used as an evaluation material for the management of sexual assault cases and a reference for subsequent researches related to sexual assault.Methods: Descriptive study was carried out using medical records and visumetrepertum of sexual assault victims who underwent vaginal swab examination at Dr. HasanSadikin General Hospital, Bandung from2010 to2014. Of 62 medical records which met the inclusion criteria, 3 were excluded. A total of 59 medical records were included as study subjects. Data taken were victimsâ age, sexual assaultâs time, examination time, penile penetration and intra-vaginal ejaculation history, also vaginal swab and STI examination result.The data were processed and presented using a frequency distribution table.Results: Spermatozoa were found in 13 cases (22.03%). Spermatozoa were found at latest 96 hours since assault. None of the victims was detected with STI.Conclusions: The successful rate of Spermatozoa detection by conducting vaginal swab in Dr. HasanSadikin General Hospital, Bandung is 22.03%. Spermatozoa can be detected even 72 hours post assault.